Comparative study of some hormonal treatment regimens for inactive ovaries in cross- breeds cows - Habeb, Asaad T.; Alyasiri, Enas A.; Homedawi, Talib M. Al; Ismaeel, Maythem A. (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to investigate the efficiency of different hormonal regimes used for treated post-partum inactive ovaries in local cross breed cows. The experimental conducted between October 2019 to April 2020. Thirty anestrous lactating cross – breed cows suffered from inactive ovaries at day 60-90 days postpartum their age was between 3-5 years old in Al-Zab city / Kirkuk province. These cows were divided randomly into three equal groups (10 cow on each one) according to the type of treatment was used, 1st group was treated by CIDR for 10 days and immediately withdrawal CIDR injected with 500 IU/ PMSG/ IM, 2nd group was treated with injected 500 IU/ PMSG/ IM, 3rd group was treated by CIDR only inserted intra-vaginal for 10 days, cows observed estrus were inseminated artificially. The reproductive performances (estrus response, estrus duration, no. of services / conception, pregnancy rates and days open)of treated cows were recorded. Plasma progesterone (P4) and estrogenconcentrations were estimated from each treatment group before and after treatment. The result of present study demonstrated that the using CIDR alone or with combination with PMSG revealed high percentage estrus response (80% and 100% respectively) compared with PMSG alone (40%) and shorter duration period (2.4 ± 0.63 days, 3.0 ± 0.84 days and 4.75 ± 0.72 days for CIDR with PMSG, CIDR alone and PMSG alone respectively), also, the hormonalregime of CIDR with PMSG and CIDR alone showed higher pregnancy rate (90% and 87.5 % respectively) and shorter days open (107.8 ± 8.36 days and 103.6 ± 6.43days respectively) than PMSG 500 IU alone (75% and 119.7 ± 7.52 days for pregnancy rate and days open respectively). higher (p